ASSESSING SUSTAINABILITY IN COASTAL TOURISM SECTORS OF ODISHA COAST, INDIA. - Nilay Kanti BARMAN; Goutam BERA; Mihir Kumar PRADHAN (European Journal of Geography)
Balasore is famous for its long sea beach and pleasant natural beauty. This district is noted for the river Subarnarekha, Buhdabalanga and also the extended calm sea beach. It is also bestowed with the Chandipur, Talsari and Bichitrapur sea Beach. Balasore is appreciated for its salt, Brass utensils, stone and clay works. Ayodhya, Balaramgadi, Bardhanpur, Bhusandeswar, Chandaneswar, Chandipur, Kasaphal, Langaleswar, Laxmannath, Panchalingeswar, Raibania, Remuna, Sajanagarh, Talasari, Tripisagadia and Kupari are some of the places of tourist interest. The sustainable development as a strategic tool requires a process of planning and management that brings together a series of interests and indigenous people’s concerns in the form of planning and development. The objective of this present research is to study the indigenous people’s attitude in Coastal tract of Balasore district, Odisha- towards the impacts of coastal tourism as also to suggest the strategic interventions for current problems and future needs through intensive field survey and human perception survey with the help of some statistical methods and GIS tools. The study finding suggests that the residents’ participation and co-operation is necessary to make the tourism development more sustainable.